Postural adjustments are modulated by manual task complexity - Andrea Cristina Lima; Diana Rezende Toledo; Luis Augusto Teixeira (Universidade Federal de Santa Catarina, 2009)
Daily life activities of humans are characterized by dual tasks, in which a manual task is performed concomitantly with a postural task. Based on the assumption that both manual and postural tasks require attentional resources, no consensus exists as to how the central nervous system modulates postural adjustments in dual tasks. The aim of the present study was to analyze the effect of a manual task requiring attentional resources on shoulder and ankle adjustments as a function of the direction and predictability of postural perturbation. The participants (n=6) were evaluated during the performance of a simple and a complex manual task, while the base of support was moved backward or forward. Latency of activation of the tibialis anterior and gastroc-nemius muscles and angular acceleration of the shoulder were analyzed. The results showed that execution of the complex manual task delayed postural adjustment. Moreover, this delay occurred differently depending on the direction of postural perturbation. The delay in postural adjustment occurred proximally in the case of anterior displacement of the platform, and distally in the case of posterior displacement. Postural adjustments were more affected by the attentional task than by the predictability of platform displacement. These results are consistent with the concept of an integrated control between manual actions and the maintenance of static posture.